2018
DOI: 10.1111/jnc.14454
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin‐dependent kinase II and memory destabilization: a new role in memory maintenance

Abstract: In this review, we discuss the poorly explored role of calcium/calmodulin‐dependent protein kinase II (CaMKII) in memory maintenance, and its influence on memory destabilization. After a brief review on CaMKII and memory destabilization, we present critical pieces of evidence suggesting that CaMKII activity increases retrieval‐induced memory destabilization. We then proceed to propose two potential molecular pathways to explain the association between CaMKII activation and increased memory destabilization. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 128 publications
(353 reference statements)
0
12
0
Order By: Relevance
“…The malaria pathway is similar to African trypanosomiasis, as proteins associated with this pathway also all originated from blood. Cocaine addiction, amphetamine addiction, and dopaminergic synapses were also significant pathways and shared altered proteins such as protein phosphatase 1 regulatory subunit 1B (Ppp1r1b), tyrosine hydroxylase (Th), and DOPA decarboxylase (Ddc), which are all associated with dopamine synthesis, except for calcium/calmodulin-dependent protein kinase type II subunit gamma (Camk2g), which is thought to be a mediator of memory by playing an important role in memory destabilization [ 53 ]. Other pathways with top 20 enrichment score values included gastric acid secretion, adrenergic signaling in cardiomyocytes, mineral absorption, proximal tubule bicarbonate reclamation, cardiac muscle contraction, complement and coagulation cascades, insulin secretion, pancreatic secretion, amoebiasis, tyrosine metabolism, cAMP signaling pathway, aldosterone-regulated sodium reabsorption, carbohydrate digestion and absorption, endocrine and other factor-regulated calcium reabsorption, and Staphylococcus aureus infection.…”
Section: Resultsmentioning
confidence: 99%
“…The malaria pathway is similar to African trypanosomiasis, as proteins associated with this pathway also all originated from blood. Cocaine addiction, amphetamine addiction, and dopaminergic synapses were also significant pathways and shared altered proteins such as protein phosphatase 1 regulatory subunit 1B (Ppp1r1b), tyrosine hydroxylase (Th), and DOPA decarboxylase (Ddc), which are all associated with dopamine synthesis, except for calcium/calmodulin-dependent protein kinase type II subunit gamma (Camk2g), which is thought to be a mediator of memory by playing an important role in memory destabilization [ 53 ]. Other pathways with top 20 enrichment score values included gastric acid secretion, adrenergic signaling in cardiomyocytes, mineral absorption, proximal tubule bicarbonate reclamation, cardiac muscle contraction, complement and coagulation cascades, insulin secretion, pancreatic secretion, amoebiasis, tyrosine metabolism, cAMP signaling pathway, aldosterone-regulated sodium reabsorption, carbohydrate digestion and absorption, endocrine and other factor-regulated calcium reabsorption, and Staphylococcus aureus infection.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium/calmodulin-dependent kinase II (CaMKII) is a major protein in the brain that plays a role in many cellular functions and plays a key role in memory maintenance [122]. Cao and colleagues (2008) found that increasing αCaMKII expression during retrieval led to an erasure of short-term (one hour old), and remote (one month old) fear memories, but the process in which CaMKII disrupted destabilization was unknown [45].…”
Section: Molecular Mechanisms Of Memory Destabilizationmentioning
confidence: 99%
“…The calcium-calmodulin-dependent protein kinase II (CaMKII) has been widely studied for its contribution to cued and contextual fear memory consolidation (Rodrigues et al 2004) and more recently, CaMKII has been attributed a role in memory strengthening and reconsolidation (de Carvalho Myskiw et al 2014;Jarome et al 2016;Vigil and Giese 2018). CaMKII is found in close proximity to GluN2B-NMDARs in the amygdala (Rodrigues et al 2004).…”
Section: Ca2+/camkiimentioning
confidence: 99%